2017
DOI: 10.1080/21541248.2017.1318816
|View full text |Cite
|
Sign up to set email alerts
|

ELMO proteins transduce G protein-coupled receptor signal to control reorganization of actin cytoskeleton in chemotaxis of eukaryotic cells

Abstract: Chemotaxis, which is chemoattractant-guided directional cell migration, plays major roles in recruitment of neutrophils, the metastasis of cancer cells, and the development of the model organism Dictyostelium discoideum. These cells share remarkable similarities in the signaling pathways by which they control chemotaxis. They all use a G protein-coupled receptor (GPCR)-mediated signal transduction pathway to sense the chemotactic gradient to guide cell migration. Diverse chemokines activate Rac through conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 64 publications
(114 reference statements)
0
28
0
Order By: Relevance
“…Moreover, G-protein-mediated Rac1 activation is critical for actin dynamics as it activates nucleation-promoting factors required for Arp2/3 complex activation, and branched actin network formation at the leading edge of neutrophils during migration [170]. ELMO/ Dock protein complexes have emerged as critical guanine nucleotide exchange factors (GEFs) for Rac1 activation [171]. In fact, chemokines induce interaction of ELMO1 with the Gβγ subunit and subsequent translocation to the plasma membrane, where it also interacts with Dock1 to form a functional GEF activating Rac1 leading to efficient actin dynamics and chemotaxis [172].…”
Section: Signalingmentioning
confidence: 99%
“…Moreover, G-protein-mediated Rac1 activation is critical for actin dynamics as it activates nucleation-promoting factors required for Arp2/3 complex activation, and branched actin network formation at the leading edge of neutrophils during migration [170]. ELMO/ Dock protein complexes have emerged as critical guanine nucleotide exchange factors (GEFs) for Rac1 activation [171]. In fact, chemokines induce interaction of ELMO1 with the Gβγ subunit and subsequent translocation to the plasma membrane, where it also interacts with Dock1 to form a functional GEF activating Rac1 leading to efficient actin dynamics and chemotaxis [172].…”
Section: Signalingmentioning
confidence: 99%
“…1); then, the signaling components direct reorganization of the actin cytoskeleton that, in turn, drives cell movement [52]. In D. discoideum and in mammalian cancer cells, various chemokines activate Rac through several GPCR signaling pathways, leading to the formation of the complex ELMO, G and DOCK and subsequent transduction of GPCR signaling to control the reorganization of actin cytoskeleton [53].…”
Section: Gpcrsmentioning
confidence: 99%
“…The ELMO protein family in mammals consists of three transcription splicing bodies: ELMO1, ELMO2, and ELMO3. Previous studies have confirmed both distinct and identical functions of ELMO1 and ELMO2 in cell migration, cell phagocytosis, and myoblast fusion [ 5 , 12 ]. They interact with the Dock family to form ELMO/Dock180 complexes, which control Rac-mediated cytoskeletal dynamics during cell migration [ 13 17 ].…”
Section: Introductionmentioning
confidence: 70%
“…Our result is similar to those of previous studies of ELMO1 and ELMO2, in which ELMO1, ELMO2, and Dock were found to play a significant role in promoting the growth of actin polymerization to drive cell migration [ 38 , 39 ]. Furthermore, ELMO proteins as essential components of the ELMO/Dock complex directly interact with G protein and transduce GPCR signaling to control dynamic remodeling of the actin cytoskeleton by regulating Rac activation during chemotaxis [ 5 , 12 ]. However, how ELMO3 participates in regulating reorganization of the actin cytoskeleton remains unknown.…”
Section: Discussionmentioning
confidence: 99%